Peningkatan Kemampuan Pola Pikir Growth Mindset pada Anak Sekolah - Tri Septiar Syamfithriani; Azhar Natsir Ahdiyat; Elin Herlina (Journal of Innovation and Sustainable Empowerment, 2024)
Education at MA Miftahuttholibin Timbang faces challenges in providing a stimulating learning environment, especially related to limited facilities, access to training for teachers, and the lack of information technology infrastructure. Apart from that, students also face learning motivation problems and a lack of understanding about growth mindset. This research aims to implement strategies to increase understanding and application of growth mindset among students. Socialization activities are carried out to educate students about the importance of a growth mindset. The focus is to synthesize students' understanding of this growth mindset and provide relevant practice. This material leads to monitoring personal goals and increasing understanding through the use of technology as an educational tool. Mentoring programs and changing the assessment paradigm from final results to the learning process are also implemented. The results show an increase in students' understanding and acceptance of the growth mindset. Students are more active in planning personal goals and evaluating their progress. The use of technology helps deepen students' understanding of this concept. Suggestions for strengthening technological infrastructure, holding training programs for teachers, and continuing mentoring programs are given to support the implementation of a growth mindset on an ongoing basis. It is hoped that with the strategies implemented, students can apply a growth mindset in everyday life and overcome learning obstacles. It is also hoped that the implementation of this strategy can become a guide for other educational institutions in strengthening the understanding and application of growth mindset among students.